Antimicrobial Resistance in Escherichia coli Isolated from Healthy Dogs and Cats in South Korea, 2020-2022 - Bo-Youn Moon; Md. Sekendar Ali; Dong-Hyeon Kwon; Ye-Eun Heo; Yu-Jeong Hwang; Ji-In Kim; Yun Jin Lee; Soon-Seek Yoon; Dong-Chan Moon; Suk-Kyung Lim (MDPI AG, 2023)
The occurrence of antimicrobial-resistant bacteria in companion animals poses public health hazards globally. This study aimed to evaluate the antimicrobial resistance profiles and patterns of commensal E. coli strains obtained from fecal samples of healthy dogs and cats in South Korea between 2020 and 2022. In total, 843 E. coli isolates (dogs, n = 637, and cats, n = 206) were assessed for susceptibility to 20 antimicrobials. The resistance rates of the most tested antimicrobials were significantly higher in dog than in cat isolates. Cefalexin (68.9%) demonstrated the highest resistance rates, followed by ampicillin (38.3%), tetracycline (23.1%), and cefazolin (18.7%). However, no or very low resistance (0-0.6%) to amikacin, imipenem, piperacillin, and colistin was found in both dog and cat isolates. Overall, 42.3% of the isolates exhibited multidrug resistance (MDR). MDR in isolates from dogs (34.9%) was significantly higher than in those from cats (20.9%). The main components of the resistance patterns were cefalexin and ampicillin in both dog and cat isolates. Additionally, MDR patterns in isolates from dogs (29.2%) and cats (16%) were shown to encompass five or more antimicrobials. Multidrug-resistant commensal E. coli could potentially be spread to humans or other animals through clonal or zoonotic transmission. Therefore, the incidence of antimicrobial resistance in companion animals highlights the urgent need to restrict antimicrobial resistance and ensure the prudent use of antimicrobials in Korea.